2007
DOI: 10.1097/01.mjt.0000208272.42379.aa
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Headache as the Main Symptom of Acquired Cerebral Toxoplasmosis in Nonhuman Immunodeficiency Virus-infected Subjects With no Lymphadenopathy

Abstract: Headache and/or migraine, a common problem in pediatrics and internal medicine, affect about 5% to 10% children and adolescents, and nearly 30% of middle-aged women. Headache is also one of the most common clinical manifestations of acquired Toxoplasma gondii infection of the central nervous system (CNS) in immunosuppressed subjects. We present 11 apparently nonhuman immunodeficiency virus-infected children aged 7 to 17 years (8 girls, 3 boys) and 1 adult woman with recurrent severe headaches in whom latent ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 332 publications
0
15
0
1
Order By: Relevance
“…The infected host must therefore elaborate effective immune defense mechanisms being under permanent tight control (Aliberti, 2005). It was reported, however, that in apparently immunocompetent non-HIVinfected subjects with no peripheral lymphadenopathy, chronic latent CT was manifesting mainly with severe headaches (Desguerre & Ponsot, 1993;Khan & Correa, 1997;Prandota, 1998;Prandota, 2006;Prandota, 2007;Prandota, Sikorska, WoƂoszczuk, & Dzik, 1988;Triki & Couvreur, 1971;Vukmirovits, Juhasz, Janko, & Toth, 1985). Moreover, Kang, Choi, Shin, and Lee (2006) showed that in mice infected with T. gondii, two weeks administration of dexamethasone resulted in depression of type T H 1 immune responses, followed by an increase in the number of parasites in the brain (Casciotti, Ely, Williams, & Khan, 2002;Wang, Claflin, Kang, & Suzuki, 2005).…”
Section: Cerebral Toxoplasmosismentioning
confidence: 99%
“…The infected host must therefore elaborate effective immune defense mechanisms being under permanent tight control (Aliberti, 2005). It was reported, however, that in apparently immunocompetent non-HIVinfected subjects with no peripheral lymphadenopathy, chronic latent CT was manifesting mainly with severe headaches (Desguerre & Ponsot, 1993;Khan & Correa, 1997;Prandota, 1998;Prandota, 2006;Prandota, 2007;Prandota, Sikorska, WoƂoszczuk, & Dzik, 1988;Triki & Couvreur, 1971;Vukmirovits, Juhasz, Janko, & Toth, 1985). Moreover, Kang, Choi, Shin, and Lee (2006) showed that in mice infected with T. gondii, two weeks administration of dexamethasone resulted in depression of type T H 1 immune responses, followed by an increase in the number of parasites in the brain (Casciotti, Ely, Williams, & Khan, 2002;Wang, Claflin, Kang, & Suzuki, 2005).…”
Section: Cerebral Toxoplasmosismentioning
confidence: 99%
“…On the other hand, however, population data indicate also that female sex may be a risk factor for chronic frequent headache (Wiendels et al, 2006). Moreover, our recent study also showed that among apparently immunocompetent patients with recurrent severe headaches caused by the increased intracranial hypertension due to reactivation of latent CT, were seven females and only three males (Prandota, 2007). Naturally occurring sexual dimorphism has been implicated in the risk, progression and recovery from numerous neurological disorders that could result from estrogen wide range of effects modulating cytokine expression in the CNS coupled with gender differences of cytokine production (CzƂonkowska, Ciesielska, Gromadzka, & Kurkowska-Jastrz ebska, 2005).…”
Section: Female Predominancementioning
confidence: 72%
“…These pathologic changes, as well as a nonspecific fever, headaches, disturbances in mental status, and focal neurological deficits may be the only manifestations of CT (Sell et al, 2005). Moreover, recently we found that the recurrent severe headaches in non-HIV-infected apparently immunocompetent subjects were due to reactivation of latent CT (Prandota, 2007;Prandota, 2007a;Prandota, 2008). Other authors also described single cases of aseptic meningitis and/or evidence for the increased intracranial pressure caused by T. gondii in apparently immunocompetent hosts without underlying illness and risk factors (Triki & Couvreur, 1971;Vukmirovits, Juhasz, Janko, & Toth, 1985;Desguerre & Ponsot, 1993;Khan & Correa, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, insulin sensitivity was found to be impaired in the patients with migraine as compared with normal individuals (P < 0.001) [817,818]. Therefore, its seems that there is a relationship between migraine/other types of headache and T1DM/T2DM, especially that many patients with recurrent headaches/migraine were found to be seropositive for T. gondii [819,820] and about two billion of people worldwide are chronically infected with the parasite.…”
Section: Possible Association Between Diabetes Migraine/other Type Omentioning
confidence: 97%